-x-4x-7=

Simple and best practice solution for -x-4x-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-4x-7= equation:


Simplifying
-1x + -4x + -7 = 0

Reorder the terms:
-7 + -1x + -4x = 0

Combine like terms: -1x + -4x = -5x
-7 + -5x = 0

Solving
-7 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -5x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -5x = 0 + 7
-5x = 0 + 7

Combine like terms: 0 + 7 = 7
-5x = 7

Divide each side by '-5'.
x = -1.4

Simplifying
x = -1.4

See similar equations:

| 10x+1=ax+b | | f(-5)=9x+7 | | .25(11+5b)=19 | | 7(8-1)= | | 4z^2-5z+(m-3)=0 | | 88=5x-3(-3x+22) | | 88=5x-3(-3x-22) | | -5=3G+4 | | 6(4-6n)=-34-7 | | 5x+8y=40fory | | 5(m+4)=30+5c | | -15+23=-2(x+8) | | -5=13g+4 | | 20+(30*x)=40+30(1-x) | | 2x+12=8x-2 | | 3y+3+y=12 | | -2(7-3v)=-2 | | 0.10(x-5)=2.40 | | -5(c-2)=30+5c | | 5t-8+4t=19 | | -5x+3x=-12 | | 12=12b-4 | | 44=-7x-3(-x-4) | | -15+23=-2(x-8) | | -24=-8k-4k | | 6r^2+36=-33r | | a-4-2=-6 | | 2400+250x=6000 | | 4x-(x+2)= | | 232=40t | | 4G=20 | | 5=-7x+6x |

Equations solver categories